Analysis of utilization of bisphosphonates, strontium ranelate and denosumabe in Serbia, Finland, Norway and Denmark in the period 2013-2016 - Cvjetković Đurđa M.; Cvjetković-Nedeljković Sara M.; Martić Nikola B.; Sabo Ana J.; Tomić Zdenko S.; Milijašević Boris Ž. (Srpsko lekarsko drustvo, 2019)
Introduction: Osteoporosis is the most common metabolic bone disease. Aim: This study aimed to measure the utilization of drugs affecting bone structure and mineralization in Serbia from 2013 to 2016, and to compare this data with that from countries with well-developed pharmacotherapeutic practice, such as Finland, Norway, and Denmark. Methods: The utilization of drugs is estimated using the Anatomical Therapeutic Chemical/Defined Daily Dose (DDD) methodology. The amount of total drugs consumed has been expressed in the number of Defined Daily Dose on 1000 inhabitants per day (DDD/1000 inhabitants/day). Results: In 2016, a total of 2.91 DDD/1000 inh/day of all drugs was used in Serbia of which 75.26% belonged to bisphosphonates, whereas they made 37.15% in Finland, 81.56% in Norway and 77.84% in Denmark of the total utilization of M05 drugs subclass. The most frequently used bisphosphonate in Serbia in 2013 was alendronic acid, while in 2016 it was ibandronic acid. In three compared countries the rate of utilization among bisphosphonates was the highest for alendronic acid. The level of other bisphosphonates' utilization in Serbia, as well as the utilization of strontium ranelate, is constantly low compared to other drugs. In comparison to other countries, the utilization of denosumab in Serbia is multiple folds lower, however with an upward trend. Conclusions: The utilization of drugs affecting bone structure and mineralization in the examined period in Serbia compared to Finland, Norway and Denmark is three to six fold lower. Furthermore, there is a difference between the structure of prescribed and consumed drugs.